DAMPAK KEPUTUSAN MANAJER TERHADAP BIAYA STICKY - Ivena Tiono; Zaenal Fanani (FEBI IAIN Langsa, 2017)
This study examines the concept of new cost behavior and is often referred to as sticky cost behavior. Traditional cost behavior says that costs will go up anddown at the same rate as sales and sales go up. This study breaks traditional cost behavior and proves that every 1% increase in cost of sales will rise by 31% but any 1% decrease in sales costs will fall by only 20%. The purpose of this study is to seek empirical evidence as to whether adjustment costs, which illustrate managerial decisions made intentionally, have an effect on sticky costs and whether the sticky costs of manufacturing and non-manufacturing industries differ. This study was tested by using multiple regression analysis and tested on all companies listed in Indonesia Stock Exchange in 2014 - 2016. The results showed that the cost of adjustment to influence sticky costs significantly. Manufacturing and non-manufacturing industries have different sticky costs, where the manufacturing industry is more sticky than the non-manufacturing industry.